Ultrasound lymph node examination of the lower extremities - Weskott, Hans-Peter (Phlebologie, 2020)
Sonography is used to detect and characterize palpable resistance or accidentally discovered lymph nodes (LN) of the lower extremities. In most cases, these are chronically inflammatory or reactive lymph nodes without clinical relevance. They are almost always found only in the groin, while LN only occur very rarely in the popliteal. In addition to the patient’s medical history and clinic, B-scan sonography and vascular architecture also play a decisive role in differential diagnosis. Due to the unspecific sonographic findings, it is not always possible to differentiate reliably between inflammatory and lymphoma diseases in a singular LN: Therefore, a thickening of the cortex with preserved vascular architecture, for example, is found in lymphomas as well as in inflammation-reactive LN. An US targeted biopsy can be diagnostically helpful. A metastatic transformation often goes hand in hand with the destruction of the LN architecture and the orderly vascular image. Also important is the LN delimitation and central ischemia in the color-coded and contrast-enhanced sonography.
Keywords: lymph nodes; differential diagnosis; lower extremity; Lymphknoten; Differenzialdiagnose; untere Extremität